Case Report pada Ibu Nifas dengan Mastitis Ringan 20 Hari Pasca Salin yang Aktif Menyusui - Icha Amelia Kusuma Wardani; Sulikah .; Agung Suharto; Tutiek Herlina (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Mastitis is an inflammation of the breast tissue commonly occurring during the postpartum period. This case report aimed to describe midwifery care for a mother 20 days postpartum with mild mastitis who continued breastfeeding. A case report approach with SOAP documentation was used. The patient experienced breast pain and swelling due to milk stasis and improper latch. Midwifery care included breastfeeding education, breast care, and warm and cold compresses, resulting in reduced symptoms while maintaining successful lactation. Appropriate midwifery care can effectively manage mild mastitis and support successful breastfeeding.